2012
DOI: 10.3390/ijms13078364
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Association of DNA Methyltransferases Polymorphisms with Gastric Cancer in the Southern Chinese Population

Abstract: DNA hypomethylation and/or hypermethylation are presumed to be early events in carcinogenesis, and one or more DNA methyltransferases (DNMTs) have been suggested to play roles in carcinogenesis of gastric cancer (GC). However, there have been no systematic studies regarding the association between DNMT gene polymorphisms and GC risk. Here, we examined the associations of 16 single nucleotide polymorphisms (SNPs) from DNMT1 (rs2114724, rs2228611, rs2228612, rs8101866, rs16999593), DNMT2 (rs11695471, rs11254413)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 49 publications
3
26
2
1
Order By: Relevance
“…The relationship between rs36012910 A>G polymorphism and risk of GC, may be due to the linkage disequilibrium with functional polymorphism rs1550117. In Yang's and our studies, no any relationships between rs1550117 with susceptibilities to GC were observed (Yang et al, 2012). Other studies also failed to find significant associations between tag SNPs of DNMT3a and breast cancer risk, or ovarian carcinoma (Mavaddat et al, 2009;Kelemen et al, 2010).…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…The relationship between rs36012910 A>G polymorphism and risk of GC, may be due to the linkage disequilibrium with functional polymorphism rs1550117. In Yang's and our studies, no any relationships between rs1550117 with susceptibilities to GC were observed (Yang et al, 2012). Other studies also failed to find significant associations between tag SNPs of DNMT3a and breast cancer risk, or ovarian carcinoma (Mavaddat et al, 2009;Kelemen et al, 2010).…”
Section: Discussioncontrasting
confidence: 68%
“…Several studies have found that DNMT3a is over-expressed in human cancers, suggesting that it may be involved in tumorgenesis and tumor progression (Ding et al, 2008;He et al, 2011;Yang et al, 2011). Recently, DNMT3a SNPs rs1550117 and rs13420827 were also found to be significantly associated with GC (Fan et al, 2010;Wu et al, 2012;Yang et al, 2012). The aim of this study is to confirm the formerly reported association between the DNMT3a polymorphisms and GC in a large number of Chinese subjects, as well as to examine the association with H.pylori infection and GA.…”
Section: Dnmt3amentioning
confidence: 61%
See 3 more Smart Citations